A review on catalytic oxidation of soot emitted from diesel fuelled engines - Neha; Prasad R.; Singh S.V. (My University, 2025)
In this review, the soot formation mechanism with an emphasis on their molecular structure is discussed, understanding of which is important to develop novel catalysts for soot oxidation. Further, a critical review of current catalytic soot oxidation scenario has been presented in this work. The various aspects affecting the activity of soot oxidation catalysts have been highlighted. The un-catalyzed and catalyzed (ceria based catalysts) kinetic soot oxidation models have also been examined. Recent advancements in catalyst design with a focus on the highly stable catalyst for soot oxidation have been given more emphasis considering their practical importance. A brief account of the notable work done on the exploration of novel soot oxidation catalysts via combinatorial catalysis is also being made. © 2020 Elsevier Ltd.